Hamman syndrome. A case report - Osvaldo Barrios Viera; Marleny González Machín (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2023)
Hamman's syndrome is characterized by the presence of free air in the interstitial space of the mediastinum, associated with subcutaneous emphysema. The case of a 19-years-old male patient, referred to the General Surgery Service of the Leopoldito Martínez General Teaching Hospital, presenting with moderate intensity dyspnea, accompanied by a sudden increase in volume of the neck and anterior region of the thorax, after a coughing fit during an acute attack of bronchial asthma is presented. The physical examination identified subcutaneous emphysema in the neck, thorax, anterior wall of the abdomen and upper limbs. A positive Hamman sign was observed. Chest X-ray and simple computed tomography were indicated, showing subcutaneous emphysema and pneumomediastinum. It was concluded as a Hamman syndrome. The treatment was conservative and the evolution was satisfactory. Hamman's syndrome is a rare and self-limiting entity that generally occurs in young, apparently healthy male patients. The diagnosis is defined by imaging studies and conservative treatment is recommended. This case is presented with the aim of exposing the presentation, diagnosis and treatment of this syndrome.